Evaluating the Implementation of an IMTAQ-Based School Program Through the Pancasila Student Profile Strengthening Project at a Public Senior High School in Palembang - Sugiyono, Sugiyono; Ismail, Fajri; Karoma, Karoma; Hamidah, Hamidah; Wigati, Indah (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study evaluates the implementation of an IMTAQ-based school program integrated with the Pancasila Student Profile Strengthening Project (P5) at SMA Negeri 6 Palembang. The program is intended to strengthen students’ religious character, discipline, responsibility, and social awareness through school culture and project-based learning.This study used a qualitative evaluative case study design based on the CIPP model, covering context, input, process, and product evaluation. Data were collected from 28 informants, including school leaders, teachers, students, school committee representatives, education staff, and supporting personnel. Data collection involved semi-structured interviews, observations, focus group discussions, and document analysis. The data were analyzed through data condensation, coding, data display, conclusion drawing, and verification. Trustworthiness was ensured through source triangulation, method triangulation, member checking, prolonged observation, and audit trail.The context evaluation showed strong alignment between the school’s vision, religious culture, P5 policy, and IMTAQ values. The input evaluation indicated adequate teacher readiness, facilities, planning documents, funding, and stakeholder support, although teacher capacity in integrating IMTAQ values varied. The process evaluation revealed structured implementation through religious habituation, project activities, teacher coordination, and supervision, but classroom-level integration and parental involvement were not fully consistent. The product evaluation showed positive changes in students’ religious behavior, discipline, politeness, social awareness, and creative project outputs, while community impact and sustainability planning still required strengthening.The IMTAQ-based P5 program has strong potential as a contextual model of character education, but future improvement should focus on teacher mentoring, operational assessment rubrics, student reflection, broader community involvement, and systematic follow-up evaluation.